Branched Polyvinyl Alcohol Hybrid Membrane for Acid Recovery via Diffusion Dialysis. Issue 6 (10th April 2019) - Cheng, Congliang; Li, Ping; He, Yubin; Hu, Xianhai; Emmanuel, Kamana
Abstract: A branched polymer was prepared by grafting allyltrimethylammonium chloride onto polyvinyl alcohol (PVA) via free‐radical polymerization. Afterwards, a series of hybrid membranes were prepared by sol‐gel cross‐linking between quaternary ammonium‐PVA and tetraethoxysilane. The obtained membranes were characterized in terms of infrared spectroscopy, ion exchange capacity, water uptake, linear expansion ratio, and acid resistance. The thermal properties of the membranes were investigated as well. The diffusion dialysis performances of the membranes were tested by using a simulated feed solution containing HCl and FeCl2 . The diffusion dialysis coefficients and the separation factors were much better than those of the commercial DF‐120 membrane. Abstract : Branched polyvinyl alcohol (PVA)‐based hybrid anion exchange membranes were prepared via sol‐gel reaction between PVA grafted with poly(allyltrimethylammonium chloride) and tetraethoxysilane. With increasing grafting ratio, the ion exchange capacity increased. Balancing flux and selectivity, membrane D can be selected as a diffusion dialysis membrane to recover acid from acidic waste liquid.